Electrolytic process applied with addition of salts for color removal in drinking water treatment - Moreira-Colletti, Gustavo; Pereira-Tangerino, Edson; Sánchez-Ortiz, Iván Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this paper the electrolytic process application as a water purification treatment stage from the Ipê neighborhood lake (Ilha Solteira –São Paulo, Brazil–) was evaluated. The treatment efficiency for apparent and true color removal, in samples by addition of humic substances, to reach different colors levels was determined. It was monitored the 1 g/L NaCl and TiO2 addition individual effect. The removal efficiency for each trial in samples taken from the electrolytic reactor each 10 minutes during one hour, were calculated.For the water sample with initial apparent color of 25 Hu, it was reduced up to 15 Hu –maximum permitted value according the Brazilian drinking water guidelines– after 30 reaction minutes. For the apparent water color with 66 Hu, with sodium chloride addition, a reduction up to 13 Hu was measured after one hour reaction. In the trials with humic substances addition, the apparent color removal for water with 708 and 247 Hu, were 87.3 % and 84.2 %, respectively, after 60 minutes of reaction.The results showed the electrolytic process performance with use of salts as a drinking water treatment stage, both for the apparent color reduction below the maximum permitted values defined by the legislation, as for its removal up to certain levels, treatment stage that should be complemented by additional stages.